A promising technology based on photoelectrocatalysis against Mycobacterium tuberculosis in water disinfection. Issue 5 (23rd February 2021) - Brugnera, Michelle Fernanda; Miyata, Marcelo; Zocolo, Guilherme Julião; Gonçalves Tessaro, Leticia Louize; Fujimura Leite, Clarice Queico; Boldrin Zanoni, Maria Valnice
ABSTRACT: Mycobacterium tuberculosis is highly infectious, persistent and has been detected in more than one quarter of the world's population. It is notoriously resistant to sterilization and disinfection procedures, largely due to an unusual hydrophobic cell wall and effective defense mechanisms against oxidative stress. This work shows an effective method to reduce M. tuberculosis quantity in water by using Ti/TiO2 nanotubes electrodes bare and coated with Ag nanoparticles by using photoelectrocatalytic oxidation process. The results have indicated 99.999% of inactivation of a solution spiked with standard and resistant strains of 1×10 4 CFU mL −1 M. tuberculosis after 5 min of treatment at Ti/TiO2 photoanode in 0.05 mol L −1 Na2 SO4 (pH 6) under applied potential of + 1.5 V versus Ag/AgCl and UV irradiation. The mycobacteria degradation was monitored by dissolved total organic carbon (TOC) removal, carbohydrate release, chromatography coupled to mass spectroscopy measurements and it is slightly superior to photocatalysis and photolysis processes. All the results corroborated with the complete inactivation and degradation of the byproducts generated during cell lysis. GRAPHICAL ABSTRACT: UF0001